Efektivitas Suplementasi Vitamin A terhadap Kejadian Infeksi Saluran Pernapasan Akut pada Balita - Eni Folendra Rosa (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Acute Respiratory Infections (ARIs) is still a cause of high morbidity and mortality in children under five in worldwide and contributes to one third of under-five deaths in developing countries. Vitamin A deficiency is one of the factors causing ARIs. This study aims to determine the effectiveness of vitamin A supplementation in reducing the incidence of ARIs. Unmatched case control study observational research design with quantitative approach, the research subjects were mothers of children under five aged 12-59 months in Ogan Komering Ulu District (OKU), South Sumatra Province. Case and control group sampling with a ratio of 1:3 so that the sample size is 228 people. Data analysis included univariate to calculate the frequency distribution of research subject characteristics, bivariate with chi-square test and multivariate using logistic regression test. The results of studies of children under five who do not get vitamin A twice a year have a 2.1 times greater risk of ARIs than childrens who get vitamin A twice a year. This study concludes that childrens who do not get vitamin A twice a year have a greater risk of experiencing ARIs than childrens who get vitamin A twice a year and based on the magnitude of the risk that can be prevented, supplementation of vitamin A is still effective in reducing the incidence of ARIs in childrens in OKU District